Persepsi Mahasiswa Program Studi Pendidikan Geografi Terhadap Sistem Pembelajaran Online pada Masa Pandemi Covid-19 - Nurvita (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2020)
Indonesia is one of the developing countries affected by Covid-19. The development of Covid-19 has increased in recent months. This research is descriptive quantitative. The population in the study was 95 students of the Geography Study Program of Tadulako University. The number of populations equals the number of samples. Primary data and secondary data were used in this study. Data processing by grouping the results of questionnaires, and calculating percentages. The data was collected by survey method and analyzed using Rank Spearman non-parametric statistic method. The findings of the study are to know the perception of geography education study program students towards the online learning system so that it can be used to overcome learning problems during the Covid-19 pandemic. Perception of the course is limited to two courses. The results showed that students' perception of geography education study program towards online learning system during the Covid-19 pandemic for Geography Learning and Teaching Strategies courses is low while geography learning evaluation courses are moderate. Students' skills using the internet in geography students for Geography Learning and Teaching Strategies courses and Geography Learning Evaluation are at a moderate level. The implementation of online learning system must be supported by all students and all parties. Online learning system is expected to be one of the solutions in learning during the Covid-19 pandemic, so as to reduce the spread of Covid-19.